(untitled) (International Journal of Engineering and Computer Science, 2014)
The information on the web search engine is escalating alarmingly and the efficiency of the information generated depends on the way of retrieving the information. There are several models which help to retrieve the pertinent information. In Information Retrieval system, the generated outputs are ranked according to their relevance. Thus information retrieval process commences as soon as the user inputs a query to hunt sufficient information. The aim of information retrieval system is to retrieve the documents attaining the user query. This paper expounds the architecture of the search engine and several different information retrieval models such as Boolean model, Vector space model, Latent semantic Indexing (LSI) model and Latent Dirichlet allocation (LDA) model. It also covers the comparative analysis of these models.